EFFECTIVE FORMS AND METHODS OF FORMATION OF CREATIVE ABILITY OF FUTURE MUSIC TEACHERS THROUGH COOPERATION TEACHING TECHNOLOGIES - Guzal Davronova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, important aspects of effective principles, forms, tools, and methods of forming creative abilities of future music education teachers through collaborative teaching technologies are scientifically and theoretically studied.